2019
DOI: 10.1016/j.palaeo.2017.11.059
|View full text |Cite
|
Sign up to set email alerts
|

A diverse trackway-dominated marine ichnoassemblage from the Lower Triassic in the northern Paleotethys: Ichnology and implications for biotic recovery

Abstract: Here, we document a diverse ichnoassemblage from the marine interbeds of the Lower Triassic terrestrial succession in the Houzhougongmiao (HZGM) section of Shaanxi Province, western North China. The integrated biostratigraphic data (bivalve, palynology and conchostracan) reveals that the ichnofossil-bearing marine beds are Griesbachian (Induan, Early Triassic) in age. The marine interbeds are interpreted as the result of the earliest Triassic transgression of the Paleo-Tethys Ocean northward to the southern ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…The Liujiagou Formation has an extremely sparse fauna and flora, but an Early Triassic age is supported by common microbially induced sedimentary structures (MISS) in the mudstones, which globally are a common feature formed after mass extinctions (Bottjer & James, 1999;Sheehan & Harris, 2004;Chu et al, 2015aChu et al, , 2017Tu et al, 2016) , 1980a,b;Shu & Norris, 1988). These fossils are part of the gradually recovering ecosystem after the PTB extinction and confirm its age as late Early Triassic (Institute of Geology, Chinese Academic of Geological Sciences, 1980a,b;Shu & Norris, 1988;Ouyang & Norris, 1999;Nesbitt et al, 2010;Feng et al, 2017;Shu et al, 2018).…”
Section: Biostratigraphy and Datingmentioning
confidence: 80%
“…The Liujiagou Formation has an extremely sparse fauna and flora, but an Early Triassic age is supported by common microbially induced sedimentary structures (MISS) in the mudstones, which globally are a common feature formed after mass extinctions (Bottjer & James, 1999;Sheehan & Harris, 2004;Chu et al, 2015aChu et al, , 2017Tu et al, 2016) , 1980a,b;Shu & Norris, 1988). These fossils are part of the gradually recovering ecosystem after the PTB extinction and confirm its age as late Early Triassic (Institute of Geology, Chinese Academic of Geological Sciences, 1980a,b;Shu & Norris, 1988;Ouyang & Norris, 1999;Nesbitt et al, 2010;Feng et al, 2017;Shu et al, 2018).…”
Section: Biostratigraphy and Datingmentioning
confidence: 80%
“…Trace fossils in the ichnogenus Biformites are most commonly attributed to ancient ophiuroid movement (Schlirf 2012; Feng et al 2019). Lower Triassic traces from central China, which resemble some of the traces produced in our study, were identified as Biformites zhadaensis (Feng et al 2019) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of a fossil trackway to trackways produced in lab setting. A ) Modified from Feng et al (2019). Biformites in the Triassic Sunjiagou Formation of Shaanxi Province, northwestern China preserved as convex epirelief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace fossils were first applied to the analysis of the causes of the end‐Cretaceous mass extinction (Savrda, 1993). Subsequently, more and more ichnologists employed the marine ichnological records across the EPME to assess the pattern of marine ecosystems (Beatty et al, 2008; Cao & Zheng, 2009; Chen et al, 2011, 2012, 2015; Cribb & Bottjer, 2020; Dineen et al, 2019; Feng et al, 2018, 2022; Feng, Chen, Benton, et al, 2019; Feng, Chen, Bottjer, et al, 2019; Feng, Chen, Woods, & Fang, 2017; Feng, Chen, Woods, Wu, et al, 2017; Guo et al, 2019; Hofmann et al, 2015; Knaust, 2010; Luo et al, 2016, 2017, 2019, 2020, 2021; Pietsch & Bottjer, 2014; Rodríguez‐Tovar & Uchman, 2006; Savrda, 2018; Shi et al, 2015, 2019; Twitchett, 2006; Zhang et al, 2018; Zonneveld et al, 2010) through analysing different ichnological parameters (e.g., bioturbation index, abundance, ichnodiversity, burrow sizes, tiering level). However, understanding the variation of terrestrial trace‐making animals is far behind the marine records around the EPME (Hasiotis, 2002).…”
Section: Introductionmentioning
confidence: 99%